Double annulation of ortho- and peri-C–H bonds of fused (hetero)arenes to unusual oxepino-pyridines. Issue 39 (3rd June 2020) - Shankar, Majji; Rit, Raja K.; Sau, Somratan; Mukherjee, Kallol; Gandon, Vincent; Sahoo, Akhila K.
Abstract : Direct difunctionalization of chemically distinct ortho - and peri -C–H bonds of fused hetero(arenes) is illustrated through an unusual one-pot domino [4 + 2] & [5 + 2] double annulation with alkynes for the first time. Abstract : Direct difunctionalization of chemically distinct ortho - and peri -C–H bonds of fused hetero(arenes) is illustrated through an unusual one-pot domino [4 + 2] & [5 + 2] double annulation with alkynes for the first time. This process is viable under Ru(ii )-catalysis using a sulfoximine directing group and builds four bonds [(C–C)–(C–N) and (C–C)–(C–O)] in a single operation. Such synthetic manifestation offers access to uncommon [6, 7]-fused oxepino-pyridine skeletons. DFT calculations provide mechanistic insight into this double annulation of naphthoic acid derivatives with alkynes and corroborate the participation of a ruthena-oxabicyclooctene intermediate, which is responsible for the rare 7-membered ring formation.